Nanoliposomes Meet Folic Acid: A Precision Delivery System for Bleomycin in Cancer Treatment - Shakiba, Davoud; Mohammadiun Shabestari, Aida; Mokhtari, Tahere; Khanlari Goodarzi, Mahyar; Saeed, Saboor; Zinatbakhsh, Zeinab; Akaberi, Kiomars; Allahyartorkaman, Mohammadreza (Asian Pacific Journal of Cancer Biology, 2024)
Overview: The targeted administration of anticancer therapies, particularly through folate receptor (FR)-mediated targeting, enhances treatment effectiveness while minimizing side effects. This study assesses the therapeutic potential of folate-targeted liposomal bleomycin (FL-BLM) against traditional forms in treating human ovarian carcinoma and oral cancer. Methods: FL-BLM was created using the thin film hydration technique with folic acid integration for active targeting. Its efficacy was compared to non-targeted liposomal bleomycin (L-BLM) and traditional bleomycin (BLM) using the MTT assay and flow cytometry to measure G2/M phase cell cycle arrest. Results: FL-BLM demonstrated significantly greater effectiveness in reducing cell viability and inducing G2/M phase arrest in oral cancer cells (HN cells, OECM-1) and ovarian cancer cells (A2780CP) compared to L-BLM and BLM, indicating successful folate-mediated targeting. Conclusions: FL-BLM effectively targets and inhibits FR-overexpressing cancer cells, particularly in both cancers. This supports the potential of folate-mediated targeting in liposomal drug delivery systems for improving drug delivery and reducing toxicity. Future research should further explore FR-targeted therapies across various cancer types